The G20 development agenda : an Indian perspective - Shome, Parthasarathi, 1950- (Cambridge : Cambridge University Press, 2015)
Since its initiation of the financial sector reforms through a newly established global cooperation process in the post-2008 financial and economic crises, the G20 expanded its agenda to include development pillars as the global economy began to recover in 2010. It actively extended its attention to the recycling of surplus country savings for investment in infrastructure in deficit countries, to the achievement of global food and energy security, to addressing the growing financialisation of commodities and its impact on price volatility, and to the costs and benefits as well as the intent and impact of continuing energy subsidies. It began to focus on recent global initiatives on climate change and adaptation financing with global equity and economic efficiency in mind. This volume addresses such issues in the G20's development agenda and assesses their relative successes and failures, with a particular focus on how the issues are of relevance to India.
Preface -- Introduction -- Group of 20 : the development agenda -- an Indian perspective / Parthasarathi Shome, Francis Rathinam -- The development agenda -- Commodity market policy for food security : the road ahead for G20 / Rajesh Chakrabarti, Francis Rathinam, Vijay Varadi -- Recycling global surpluses for infrastructure investment in emerging market economies / Renu Kohli -- G20 : impact of the crisis with special reference to India and international burden sharing / D.K. Srivastava -- India's growth prospect : structural impediment / Kirit S Parikh -- Energy security and environmental sustainability -- The co-benefit principle and the Durban platform : towards an inclusive framework for negotiating climate finance / A. Damodaran -- Greening the G20 agenda : a way forward / Parthasarathi Shome and Amrita Goldar -- Revisiting fossil-fuel subsidies in the context of ongoing G-20 dialogue : a discussion with special reference to India / Meeta Mehra and Divya Datt -- Should India join the international energy agency? / Prodipto Ghosh -- Contributors -- Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Economic assistance -- India; Economic development projects -- Management; Economic policy -- International cooperation; India -- Economic conditions -- 21st century; Group of Twenty countries -- Economic policy